Impact of Prone Jackknife Position on Intraoperative Hypotension During Percutaneous Nephroscopy: A Retrospective Matched Analysis - Lyu S; Wu G; Wu Y (Dove Medical Press, 2023)
Song Lyu,1 Guobin Wu,2 Yingfen Wu1 1Department of Anesthesiology, The Second Affiliated Hospital of Hainan Medical University, Haikou, People's Republic of China; 2Medical Record Management Department, The Second Affiliated Hospital of Hainan Medical University, Haikou, People's Republic of ChinaCorrespondence: Song Lyu, Department of Anesthesiology, The Second Affiliated Hospital of Hainan Medical University, Haikou, People's Republic of China, Fax +8689866808208, Email Lssjk1@126.comObjective: To investigate the potential relationship between the prone jackknife position during percutaneous nephroscopy and the occurrence of intraoperative hypotension.Methods: A retrospective analysis was conducted on 651 patients who underwent percutaneous nephroscopy at the Second Affiliated Hospital of Hainan Medical University. The primary focus was to investigate the occurrence of hypotension during the surgical procedure and assess the duration of hypotensive episodes. Patients were categorized into the prone jackknife position group and the lateral position group. To compare the incidence of intraoperative hypotension between the two groups, a 1:1 propensity match was performed. Following the matching process, intraoperative hypotension was assessed and compared between the two groups before and after the match. The binary logistic regression analysis determined the probability of intraoperative hypotension occurred in each group. Furthermore, linear regression analysis was used to analyze the duration of hypotensive episodes experienced by patients in both groups.Results: After propensity score matching, a total of 272 patients with similar characteristics were obtained (136 in each group). The prone jackknife group had a significantly higher incidence of intraoperative hypotension than the lateral group after the match, with an odds ratio of 2.71 (95% confidence interval: 1.595- 4.605). Binary logistic regression analysis showed that age and body position exhibited statistical significance as risk factors. Linear regression analysis before and after the match indicated that the duration of hypotension was associated with age, surgical time, and a history of hypertension.Conclusion: The prone jackknife position syndrome after general anesthesia could occur in surgeries. The position could contribute to the development of hypotension during the percutaneous nephroscopy procedure.Keywords: prone, jackknife position, percutaneous nephroscopy, intraoperative hypotension